The Relationship Between Teachers’ Perceptions Towards Principal’s Transformational Leadership and Their Organizational Commitment in Yuehe Town Junior High School, China - Chen, Jinxue (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this study is to explore the relationship between teachers’ cognition of principals’ transformational leadership and their organizational commitment in Yuehe Town Junior High School, Tongbai County, Henan Province, China. This study took 65 full-time teachers as the research object and conducted a questionnaire survey. Means and standard deviations are used to determine teachers’ cognitive level of school principals’ transformational leadership and organizational commitment, and the Pearson product correlation number is used to analyze the relationship between teachers’ perceptions towards principal’s transformational leadership and their organizational commitment. In order to analyze the relationship between the two variables, Pearson product moment correlation coefficient was used, the results show that the teachers of the target school hold a relatively positive attitude towards the principal’s transformational leadership, and the level of their organizational commitment was high. Pearson correlation test shows that there is a significant correlation between junior high school teachers’ cognition of principals’ transformational leadership and their organizational commitment in Yuehe Town Junior High School, Henan Province, China.